Estrutura e robustez de redes de interação parasito-hospedeiro peixe. - Bellay, Sybelle (2013)
The organization of interspecific interactions in ecological networks of host-parasite reflects mainly the biology and ecology of species, well as coevolutionary processes. Aspects of the organization and robustness of interaction of parasite-host fish networks were analysed. Binary interactions of ecto- and endoparasites with their hosts for 22 different aquatic environments were evaluated. Significant differences were observed between organizational network parameters, which endoparasites tend to have higher values of species richness per host, residual connectance and nestedness, as well as lower values of modularity. The composition of host species in modules of ecto- and endoparasites networks presented low similarity, and the ectoparasites were more sensitive to the loss of host species, with low contribution to the network robustness. Besides, interactions of parasite-host network of the Guandu River, located in the Brazilian Atlantic Forest, were quantitatively analyzed.. Hosts tended to present low susceptibility to parasites, while these usually present elevated levels of dependency. The asymmetry and the interaction strength (IS) were related to the host phylogeny. Although these parameters are unrelated to the parasite phylogeny, there was a tendency for differences among values of IS for taxonomic groups of parasites. This difference was also observed among the groups for complementary specialization (d'), however this was unrelated with the species phylogeny. No correlation was observed between d' and IS of the hosts, however for the parasites there was a positive correlation. High values of complementary specialization of the network and modularity, besides low values of connectance and nestedness were observed, which are expected for networks with many specific interactions. Furthermore, in this study was verified that the removal of a host with many interactions (degree) or high IS might cause greater effects than the removal of a species with high abundance of parasites or d', reflecting the influence of specificity and dependence of the interactions in the ecological network organization.